Reconsiderations on Adhesion Control for Locomotive HXD1C and HXD1 - WU Xin-hong; GAO Shou-cong; ZHANG Jian-bai; ZENG Yun; ZHANG Zheng-fang; DING Pei-yi (机车电传动)
Adhesion control condition of locomotive HXD1C and HXD1 was introduced. For the traction demand of electric locomotive HXD1C and HXD1, corresponding improvement of adhesion utilization control software was proposed. Adhesion control strategy based on indirect adhesion force control was offered, and experiment data was given at the same time. The result effectively proved the high performance of adhesion control software for electric locomotive HXD1C and HXD1 in the heavy and high-speed transport modes.